EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM KETERAMPILAN MENULIS PARAGRAF NARASI SISWA SEKOLAH DASAR - Budi Febriyanto (Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the problem of the skill of writing low student narrative paragraphs. This study aims to examine differences in skills in writing narrative paragraphs of elementary school students between experimental classes that apply the Cooperative Integrated Reading and Composition learning model to the control class that applies conventional learning. In this study a quantitative approach was used with the quasi-experimental method. The research design uses Nonequivalent Control Groups Design (NCGD). The research sample was 30 students of Cicenang I Elementary School in VA class as the experimental class and 30 students of Cicenang I Elementary School in class as the control class. Data collection tool in the form of a question sheet writing narrative paragraphs. Data collection techniques in the form of tests, namely prates to measure the initial ability to write narrative paragraphs of students and post-test to see the final ability of narrative paragraph writing skills. Based on the results of the research it can be concluded that there are differences in the improvement of writing skills of narrative paragraphs students who obtain learning using the CIRC model in the experimental class with students who obtain conventional learning methods in the control class. Abstrak Penelitian ini dilatarbelakangi oleh masalah keterampilan menulis paragraf narasi siswa yang rendah. Penelitian ini bertujuan untuk menguji perbedaan keterampilan menulis paragraf narasi siswa sekolah dasar antara kelas eksperimen yang menerapkan model pembelajaran Cooperative Integrated Reading and Composition dengan kelas kontrol yang menerapkan pembelajaran konvensional. Dalam penelitian ini digunakan pendekatan kuantitatif dengan metode kuasieksperimen. Desain penelitian menggunakan Nonequivalent Control Groups Design (NCGD). Sampel penelitian adalah siswa SDN Cicenang I kelas VA sebanyak 30 siswa sebagai kelas eksperimen dan siswa SDN Cicenang I kelas VB sebanyak 30 siswa sebagai kelas kontrol. Alat pengumpul data berupa lembar soal menulis paragraf narasi. Teknik pengumpulan data berupa tes yaitu prates untuk mengukur kemampuan awal menulis paragraf narasi siswa dan pascates untuk melihat kemampuan akhir keterampilan menulis paragraf narasi. Berdasarkan hasil penelitian diperoleh kesimpulan yaitu terdapat perbedaan peningkatan keterampilan menulis paragraf narasi siswa yang memperoleh pembelajaran menggunakan model CIRC pada kelas eksperimen dengan siswa yang memperoleh metode pembelajaran konvensional pada kelas kontrol. Kata Kunci: Cooperative integrated reading and composition, keterampilan menulis, paragraf narasi